Microstructure changes in Zr-1Nb alloy after pulsed electron beam surface modification and hydrogenation; Surface and Coatings Technology; Vol. 284 - Pushilina N. S. Natalia Sergeevna; Kudiyarov V. N. Victor Nikolaevich; Laptev R. S. Roman Sergeevich; Lider A. M. Andrey Markovich; Teresov A. D. Anton Dmitrievich (2015, 2015)
Title screen